Pendidikan Agama Islam di Sekolah Alternatif SD Sanggar Anak Alam (SALAM) Nitiprayan Kasihan Bantul Yogyakarta - Sholihah, Zumrotus; Machali, Imam (IAIN Ponorogo, 2017)
This study is aimed at describing the implementation of Islamic Religious Education in the Alternative School of SD SanggarAnakAlam (SALAM) NitiprayanKasihanBantul, Yogyakarta with focus on curriculum, methods, evaluation, and outcomes. This qualitative approach revealed that the implementation of PAI learning in SD SanggarAnakAlam (SALAM) in term of the curriculum used was based on the need, which wasemphasized on social ethics (akhlak). The material taught was based on the environment around the students where they had experiential learning. The results achieved in learning PAI at SD SanggarAnakAlam (SALAM) were first, the cognitive aspects included the ability of students in using the mind. Second, the affective aspects, they applied the values of tolerance, not discriminating friends to learn and mingle. Theywere trained in mutual respect and regard human beings. Third, the psychomotor aspect, they did various activities of planting and caring for the garden, and arranging classes conducted every morning in groups in turn. Â ÙØ¯Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø¥ÙÙ Ø¹Ø±Ø¶ ÙÙØµÙ ØªØ·Ø¨ÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø© Ø§ÙØ§Ø¨ØªØ¯Ø§Ø¦ÙØ© Ø§ÙØ¨Ø¯ÙÙØ©